The dynamics of cytokine d nitric oxide secretion in mice injected with Tityus serrulatus scorpion venom - Vera L. Petricevich; Carlos F. Peña (Mediators of Inflammation)
Aims: The effects of Tityus serrulatus venom (TSV) were analysed with respect to the susceptibility of four isogenic mouse, the symptoms following injection of venom and the inflammatory mediators in an experimental model of severe envenomation induced in mice.